Development of a Qur'an-Integrated Student Worksheet on Newton’s Laws to Enhance Self-Regulated Learning: An ADDIE-Based Study in Islamic Junior Secondary School - Kuni Fidrotul Badingah; Ahmad Khoiri; Fatiatun (MO.RI Publishing, 2026)
Physics teaching materials in Islamic schools frequently prioritise conceptual mastery while neglecting the integration of Islamic values and the cultivation of self-regulated learning (SRL), despite both being mandated objectives of Indonesian national education. This study aimed to develop, validate, and assess the practicality and effectiveness of a Qur’an-integrated Student Worksheet (Lembar Kerja Peserta Didik, LKPD) on Newton’s Laws designed to strengthen SRL among seventh-grade students. A Research and Development design following the ADDIE model was employed. Participants comprised two expert validators (subject-matter and media specialists), one physics teacher, and 59 seventh-grade students from MTs Ma’arif Gondang, Indonesia, distributed between an experimental class (VII-A, n = 30) and a control class (VII-B, n = 29). The LKPD was evaluated for validity, practicality, and effectiveness. Expert validation yielded a mean score of 4.39 out of 5.00 (87.8%), placing the product in the “Very Valid” category. Practicality assessment by students and teacher produced a mean score of 3.70 out of 4.00 (92.5%), classified as “Very Practical”. Effectiveness was examined through a pre-test–post-test quasi-experimental design; the experimental group achieved a mean normalised gain (N-Gain) of 57%, exceeding the control group’s 42%. An independent-samples t-test confirmed a statistically significant difference (t = 2.989 > t = 1.673; df = 57; Alpha = .05). These findings indicate that Qur’an-integrated instructional materials can meaningfully advance both conceptual understanding and self-regulatory capacities in secondary physics education.